Concurrent optimization of stacking sequence and stiffener layout of a composite stiffened panel. Issue 4 (3rd April 2019) - An, Haichao; Chen, Shenyan; Huang, Hai
ABSTRACT: This article is to optimally design laminated composite stiffened panels by optimizing both stacking sequences of the panel skin and stiffeners as well as the layout of stiffeners. Starting from initial designs of stiffener layout and stacking sequences for each stiffener and the panel skin, the problem is formulated with discrete and continuous variables, where discrete 0/1 variables represent the absence/presence of each layer in initial stacking sequences, and continuous variables represent layer thicknesses. A first-level approximate problem is established to make the problem explicit. Genetic algorithm is used to determine the existence of each layer in the laminates. When the number of retained layers in stiffener becomes zero, that stiffener can be seen as unnecessary and removed. For individual fitness calculation, a second-level approximate problem is constructed to optimize continuous ply thicknesses of retained layers. Correspondingly, laminated stacking sequences and stiffener layout are concurrently optimized.